On infinite-rank singular perturbations of the Schrödinger operator - Kuzhel', S. A.; Vavrykovych, L. (Ukrains’kyi Matematychnyi Zhurnal, 2008)
Schrodinger operators with infinite-rank singular potentials $\sum^∞_{i,j=1}b_{i,j}(ψ_j,·)ψ_i$ are studied underthe condition that singular elements $ψ_j$ are $ξ_j(t)$-invariant with respect to scaling transformations in ${\mathbb R}^3$.